2020
DOI: 10.1007/s10055-020-00442-w
|View full text |Cite
|
Sign up to set email alerts
|

Designing virtual environments for attitudes and behavioral change in plastic consumption: a comparison between concrete and numerical information

Abstract: Starting from the pro-environmental potential of virtual reality (VR), the aim was to understand how different statistical information formats can enhance VR persuasive potential for plastic consumption, recycling and waste. Naturalistic, immersive virtual reality environments (VREs) were designed ad hoc to display three kinds of statistical evidence formats, featured as three different formats (i.e., numerical, concrete and mixed). Participants were exposed only to one of the three formats in VR, and their af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 49 publications
0
31
0
Order By: Relevance
“…While the field of VR for environmental education is still in its infancy, previous studies have demonstrated the potential impact that experiencing environmental issues in VR can have on promoting behavioral and emotional changes toward the environment [58][59][60].…”
Section: Main Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the field of VR for environmental education is still in its infancy, previous studies have demonstrated the potential impact that experiencing environmental issues in VR can have on promoting behavioral and emotional changes toward the environment [58][59][60].…”
Section: Main Findings and Discussionmentioning
confidence: 99%
“…Ahn and colleagues (2014) revealed that after experiencing how to cut a tree in the VR condition, participants used significantly fewer napkins to dry spilled water than participants who read a passage about cutting a tree [59]. Chirico et al (2020) also placed individuals in a virtual natural environment in order to communicate an environmental problem [60]. They investigated how VR could contribute to mitigating the plastic pollution issue while participants were transported to a garden during the spring season.…”
Section: Vr For Environmental Literacymentioning
confidence: 99%
“…An advantage of implicit measures is that no introspection on the evaluation is necessary as automatic responses were measured (De Houwer et al, 2009;Greenwald et al, 2002Greenwald et al, , 2009. Thus, responses are less prone to biases which is useful as social desirability may affect responses to environmental topics including plastic (Chirico et al, 2021;Vesely & Klöckner, 2020). Moreover, especially for (ambivalent) attitudes and behaviours that diverge, different approaches to assess related attitudes are reasonable.…”
Section: The Current Studymentioning
confidence: 99%
“…This radical transformation determines a need to educate citizens and professionals, increase their awareness, and ultimately support a behavior change towards more sustainable choices and consumer habits. To this purpose, Virtual Reality (VR) has been identified as a promising tool and investigated in many contexts and for a variety of topics and aims: for professionals and stakeholders [2][3][4], in education [5][6][7], and on subjects ranging from plastic pollution [8] to building design [2], sustainable mobility [9], tourism [7] and water management [6].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, different modalities have been explored, including immersive experiences [8,10], mobile applications [9,11], computer games [7,11], simulations [6,12], games [11,13,14], and single- [8,10,15] and multi-user [3,14] applications. Hence, designers creating VR experiences have a great number of possibilities available, with many potential features that can be varied and manipulated depending on the specific context.…”
Section: Introductionmentioning
confidence: 99%